Answer:
Three fourths of a number (x) is equal to
.Required equation is 3x-74=0.
Solution:
We need to represent the given statement as an equation.
Three fourth of a number is equal
![18 (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mpwvs0etcna6f54wh6uyslptdqtawpn2cf.png)
Let assume the number be represented by variable x.
So three fourth of the number will be
![(3)/(4) * \text { number }=(3)/(4) * x=(3 x)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/b2giwyidwtr8196ee9pizfaolibil2n230.png)
Also three fourth of a number is equal to
![18 (1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mpwvs0etcna6f54wh6uyslptdqtawpn2cf.png)
So we get
![18 (1)/(2)=(3 x)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x8mdealnq6q334y5hmcciqyoohfiei7dj8.png)
On simplifying above term,
![(3 x)/(4)=18+(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/768gdzeiz1smzkprta4ydt3uwr0p2hylt7.png)
![(3 x)/(4)=(37)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3cf60wqik9ojk53c4n7jkedgqivpp9s8ti.png)
![3 x=2 * 37](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i6bs90x1ih2pq48culbjauwrlslnj3cxau.png)
3x=74
3x-74=0
Hence required equation is 3x-74=0